Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

Psychiatrie, genre et sexualités dans la seconde moitié du XXe siècle - Arena, Francesca; Chiletti, Silvia; Coffin, Jean-Christophe (Comment s'en sortir?, 2015)
Les diagnostics cliniques et les différentes nosographies psychiatriques qui ont été établies dans la deuxième moitié du XXe siècle, notamment dans les différentes éditions du manuel américain de diagnostic et statistique des troubles mentaux (DSM), montrent qu'un nombre très significatif de troubles sont envisagés comme étant genrés. Plusieurs controverses ont marqué l'histoire de ces diagnostics depuis les années 1950 : d'abord celui des sexualités et de leurs frontières floues, ensuite la notion controversée d'identité de genre, enfin la problématique des troubles périnataux. Si le principe de différentiation constitue un élément incontournable de la pensée psychiatrique, le façonnage et l'usage du concept de « genre » révèlent des tensions entre la psychiatrie et la société (notamment les mouvements gay, féministes et trans) mais aussi au sein de la psychiatrie elle-même. Il apparaît évidant que, dans les classifications psychiatriques, les normes sociales de genre sont intégrées de manière passive et acritique, au point que l'usage du concept de genre peut amener à l'inverse à renforcer la naturalisation des comportements alors même que, dans les sciences sociales, il est utilisée pour interroger et déconstruire la prétendue naturalité de la différence des sexes.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques; violences; états-unis

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Sorcières, sages-femmes et infirmières : une histoire des femmes soignantes - Ehrenreich, Barbara; English, Deirdre (Cambourakis, 2015)
Engagées dans le Mouvement pour la santé des femmes dans les années 1970, Barbara Ehrenreich et Deirdre English enquêtent sur les racines historiques de la professionnalisation du corps médical. Portant un regard féministe sur les chasses aux sorcières en Europe et la suppression de la profession de sage-femme aux Etats-Unis, elles s'interrogent : et si, derrière ces événements, se cachait une véritable monopolisation politique et économique de la médecine par les hommes de la classe dominante, reléguant peu à peu les femmes à la fonction subalterne d'infirmière docile et maternelle ? Depuis sa parution aux Etats-Unis en 1973, cet essai concis et incisif a ouvert la voie à de nombreux travaux de recherche et prises de conscience. Cette traduction s'ouvre sur une préface inédite des deux auteures.
Keywords: approches et analyses; com5170; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; histoire; lit2815; lit3220; lit3495; occident; premier cycle; santé; santé reproductive; sciences humaines; sorcière; systèmes d'oppressions; thématiques; violences; violences gynécologiques et obstétricales

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (Collection Logiques sociales. Série Sociologie du genre, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Medical industrial complex visual - Mingus, Mia (Leaving Evidence, 2015)
The following is a visual* of the Medical Industrial Complex (MIC) and is offered as a tool for our work for collective liberation.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capacitisme; cours; discours dominant; eugénisme; fem3300; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis